PENGARUH SUCTION DAN ORAL HYGIENE TERHADAP KEEFEKTIFAN BERSIHAN JALAN NAFAS PADA PASIEN PENURUNAN KESADARAN ON VENTILATOR DI RS. ADHYAKSA JAKARTA 2025 - Emi Wahyu Pinesti; Bambang Suryadi (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2026)
Airway effectiveness is a condition when airflow from and to the lungs runs smoothly so that gas exchange is adequate. In patients with decreased consciousness who have an endotracheal tube (ETT), accumulation of secretions, decreased cough reflex, and oropharyngeal colonization increase the risk of airway obstruction and respiratory tract infections. The purpose of this study was to determine the Effect of Suction and Oral Hygiene on the Effectiveness of Airway Clearance in Patients with Decreased Consciousness on Ventilators at Adhyaksa Hospital in 2025. The method in this study used a One-group pretest-posttest design with a population and sample of 16 respondents, the instrument used was the SLKI indicator of airway clearance. The results of the study showed the effect of the combination of Suction and oral hygiene on the effectiveness of airway clearance in patients with decreased consciousness who used ventilators in the ICU at Adhyaksa Hospital, Jakarta in 2025 with a p value of 0.001 <0.05. The conclusion is that suction and oral hygiene are effective. Recommendations for suctioning and oral hygiene can be carried out on patients who experience decreased consciousness and are on a ventilator.